TINJAUAN HUKUM ISLAM TERHADAP NILAI SAKRALITAS BUDAYA MAPPANRE TEMME DALAM PERKAWINAN ADAT BUGIS BONE - Sadiani Sadiani (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri Bone, 2018)
Mappanr temme in Bugis Bone customary marriage is a form of gratitude and gratitude has been able to read and complete the Qur'an. The ability to read the Qur'an is expected to be able to be practiced in navigating the household ark. The implementation of this culture has values that contain wisdom and purpose. The value of cultural sacredness mappanr temme (khataman al-Qur'an) includes; the value of worship, the value of sennu-sennungeng, and the people's belief in the imperfection of marriage if they do not implement mappanr temme. From the value of the sacred, mappanr temme (khataman al-Qur'an) in the review of Islamic law is a culture that may be carried out and is a urf that is valid by looking at the wisdom and purpose of its implementation.